Development of a SIM Card based Key Management System - Ozdenızcı Kose, Busra; Çevikbaş, Cem; Mantar, H. Ali; Coskun, Vedat (My University, 2020)
Today, almost all applications running on the smartphone provide valuable and sensitive transactions on user’s private data such as identity data, credit card details, payment data, location data and so on. Service providers are trying to increase the efficiency of their applications and to improve the compatibility of security mechanisms through SIM (Subscriber Identity Module) cards owned by Mobile Network Operators (MNOs). In this sense, there is an urgent need for a centralized secure key management service. Thanks to the strong security infrastructure created by card manufacturers during design and the robust security procedures applied by MNOs; SIM cards have significant potential to provide the required secure environment for service providers. Accordingly, a novel centralized SIM card based key management framework called SIM-GAYS is designed and developed to facilitate centralized cryptographic operations of diverse mobile applications provided by service providers. This paper aims to present and demonstrate the essential development results of SIM-GAYS. The functional requirements of the SIM-GAYS are tested depending on developed scenarios. The results showed that the designed and developed APDU (Application Protocol Data Unit) transmission method between SIM card and smartphone, and secure storage of the keys by the Master Key (owned by SIM-GAYS) support almost all cryptographic services provided by SIM-GAYS framework.
Keywords: Bilgisayar Bilimleri; Yazılım Mühendisliği